a, Điều kiện xác định của A là
4 - x2 \(\ne\) 0
⇒ (2 - x)(2 + x) \(\ne\) 0
⇒ \(\left\{{}\begin{matrix}2-x\ne0\\2+x\ne0\end{matrix}\right.\Rightarrow\left\{{}\begin{matrix}x\ne2\\x\ne-2\end{matrix}\right.\) (điều kiện xác định)
Rút gọn:
\(A=\dfrac{x^2+4x+4}{4-x^2}=\dfrac{\left(x+2\right)^2}{\left(2-x\right)\left(2+x\right)}=\dfrac{x+2}{2-x}\)b, Vì |x + 1| = 3
⇒ |x +1| = |\(\pm\)3|
⇒ x + 1 = \(\pm\)3
⇒ \(\left\{{}\begin{matrix}x+1=3\\x+1=-3\end{matrix}\right.\)
⇒ \(\left\{{}\begin{matrix}x=3-1\\x=-3-1\end{matrix}\right.\)
⇒ \(\left\{{}\begin{matrix}x=2\left(\text{loại}\right)\\x=-4\end{matrix}\right.\)
Nếu x = -4
⇒ A = \(\dfrac{-4+2}{2-\left(-4\right)}\)
⇒ A = \(\dfrac{-2}{2+4}\)
⇒ A = \(\dfrac{-2}{6}\)
⇒ A = \(\dfrac{-1}{3}\)
Vậy A = \(\dfrac{-1}{3}\) khi |x + 1| = 3
c,
▲Nếu A = 2
⇒ \(\dfrac{x+2}{2-x}=2\)
⇒ x + 2 = 2.(2 - x)
⇒ x + 2 = 4 - 2x
⇒ x + 2x = 4 - 2
⇒ 3x = 2
⇒ x = \(\dfrac{2}{3}\)
Vậy A = 2 thì x = \(\dfrac{2}{3}\)
▲Nếu A = -2
⇒ \(\dfrac{x+2}{2-x}=-2\)
⇒ x + 2 = -2.(2 - x)
⇒ x + 2 = -4 + 2x
⇒ x - 2x = -4 + 2
⇒ - x = -2
⇒ x = 2
Vậy A = -2 thì x = 2
d, Để A ∈ Z
⇒ \(\dfrac{x+2}{2-x}\) ∈ Z
⇒ (x + 2) ⋮ (2 - x)
⇒ (2 + x) ⋮ (2 - x)
⇒ (2 - x + x + x) ⋮ (2 - x)
⇒ (2 - x + 2x) ⋮ (2 - x)
Mà (2 - x) ⋮ (2 - x)
⇒ 2x ⋮ (2 - x)
⇒ 2 ⋮ (2 - x)
⇒ (2 - x) ϵ Ư(2) = {\(\pm\)1; \(\pm\)2}
Ta có bảng sau
2 - x |
1 |
-1 |
2 |
-2 |
x |
1 |
3 |
0 |
4 |
Vậy x ∈ {1; 3; 0; 4}